Menstrual knowledge associated with adolescent’s attitude of intellectual disability on facing menstruation in Bantul, Indonesia - Yati, Dwi; Lutfiyati, Afi; Riyadi, Sujono; Hafiz, Abdul (International Journal of Research in Medical Sciences, 2020)
Background: Menstruation is an important event in puberty as a biological sign of sexual maturity for young women. Adolescent with intellectual disability has the same stage of biological development as normal adolescent. Menstruation often causes many problems such as menstrual pain, emotional changes and menstrual personal hygiene (such as: using sanitary napkins). It causes a lot of negative reactions and anxiety. The phenomenon that has often happened in community is feeling taboo to discuss menstrual problems, so that adolescents are not well informed. Objective of this study was to determine the association between menstrual knowledge with adolescent’s attitude of mental retardation (intellectual disability) on facing menstruation. Methods: This research is a descriptive analytic with a cross-sectional study. It was conducted at SLB Masudi Putra I and II Bantul, in August to October 2018 with intellectual disability adolescents who experienced menstruation, those were 39 respondents. Data collection is done by using a questionnaire. Bivariate analysis was done by the Spearman rank test. Results: The results of this research indicate that the percentages of adolescent’s knowledge of intellectual disability on facing menstruation were in medium category of 16 respondents (41.0%), and adolescent’s attitude of intellectual disability on facing menstruation mostly were negative of 24 respondents (61.5%) with p-value 0.001 (p<0.05 ) and the correlation coefficient (r) is positive at 0.495. It shows that there is an association between menstrual knowledge with adolescent’s attitude on facing menstruation with the closeness of the correlation in medium category. Conclusions: There were an association between menstrual knowledge with adolescent’s attitude of intellectual disability on facing menstruation at SLB Marsudi Putra Bantul with p-value 0.001 (p<0.05).